ZONAL DIFFERENTIATION AND CRYSTAL MORPHOTYPE CLASSIFICATION IN HUMAN SALIVA DEHYDRATION FACIES: A QUANTITATIVE MORPHOLOGICAL ANALYSIS - Ergashev Erkinjon Abdusattor ugli; Mashrabboyev Abdusamad Abdugʻani ugli; Abdug‘aniyev Asadbek Faxriddin ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Background: Morphological analysis of biological fluid dehydration patterns offers a non-invasive approach to characterizing complex physicochemical properties. Systematic quantitative classification of saliva crystallization zones and crystal morphotypes remains limited. Objective: To develop and apply a quantitative morphological classification system for zonal differentiation and crystal morphotype distribution in human saliva dehydration facies. Methods: Thirty dehydrated saliva droplets from 10 healthy male volunteers (18–30 years) were analyzed by digital microscopy (50×–200×). Five morphological parameters - zonal expression, crystal shape class, branching complexity, density, and symmetry - were scored quantitatively and analyzed statistically. Results: Three-zone organization was identified in 73.3% of droplets. Dendritic and branched morphotypes predominated (80.0%), with high structural heterogeneity (86.7%). Significant inter-individual morphological reproducibility was demonstrated (CV < 12% for all parameters). Conclusions: A reliable, reproducible quantitative morphological classification system for saliva dehydration facies is feasible and yields consistent results across individuals, supporting its application as a biophysical diagnostic tool.